Right Ventricular Outflow Tract Perforation and Stenting for a Premature Neonate with Pulmonary Valve Atresia and Double Outlet Right Ventricle - Mohammed Rasool Hussein; Maysam Yousif Abed; Nabeeha Najatee Akram (Mustansiriya Medical Journal)
Pulmonary valve atresia (PVA) is a fatal pediatric cardiac condition and commonly associated with other anomalies such as double outlet right ventricle (DORV). There is a disagreement over the best surgical strategy for treating PVA in conjunction with DORV. Prematurely born neonates are considered high-risk group for early pulmonary artery shunt surgery as the staged repair is found to be associated with higher interstage mortality, while the primary repair may lead to frequent postrepair reinterventions due to the presence of associated developmental anomalies. In this report, we present the successful results of using percutaneous transcatheterization in a high-risk patient; a 6-h premature neonate who had DORV, PVA with other anomalies including situs inversus, levocardia, D-malposed great arteries without patent ductus arteriosus. This rapid interventional catheterization offered to the neonate has an immense advantage of lifesaving and the protection against the remolding effect on the right ventricle that usually develops when waiting for the palliative procedures or surgery to take place.